INFUSING ISLAMIC VALUES AND SUSTAINABLE DEVELOPMENT INTO CHEMISTRY FOR PRE-SERVICE ISLAMIC ELEMENTARY SCHOOL TEACHERS - Muhamad Imaduddin (JURNAL PENDIDIKAN SAINS (JPS), 2019)
This paper discusses the designs in infusing Islamic values and sustainable development and how challenges must be faced in the training for pre-service Islamic elementary school teachers. The subjects of this study consisted of 77 primary school educational candidates who contracted "Simple Chemistry" lectures The instrument was The Chemical Essay Test Integrated Sustainable Development Aspects (CET-SD) containing Islamic discourse. Based on pedagogical planning, lesson plans are divided into four stages, consisting of (1) phase of contact; (2) phase of curiosity and planning; (3) phase of elaboration; and (4) phase of deepening and networking. The link between Islamic values and chemistry and the environment was well understood by pre-service teachers. Some challenges in teaching chemical content were found regarding with (1) difficulties with the relation between macro domain and submicro domain; (2) difficulties with the relation between symbolic domain and macro or submicro domain; (3) difficulties with models.